Perennializing marginal croplands: going back to the future to mitigate climate change with resilient biobased feedstocks - Ramirez, Salvador; Schmer, Marty R.; Jin, Virginia L.; Mitchell, Robert B.; Stewart, Catherine E.; Parsons, Jay; Redfearn, Daren D.; Quinn, John J.; Varvel, Gary E.; Vogel, Kenneth P.; Follett, Ronald F. (Frontiers in Energy Research, 2024)
Managing annual row crops on marginally productive croplands can be environmentally unsustainable and result in variable economic returns. Incorporating perennial bioenergy feedstocks into marginally productive cropland can engender ecosystem services and enhance climate resiliency while also diversifying farm incomes. We use one of the oldest bioenergy-specific field experiments in North America to evaluate economically and environmentally sustainable management practices for growing perennial grasses on marginal cropland. This long-term field trial called 9804 was established in 1998 in eastern Nebraska and compared the productivity and sustainability of corn (Zea mays L.)-both corn grain and corn stover-and switchgrass (Panicum virgatum L.) bioenergy systems under different harvest strategies and nitrogen (N) fertilizer rates. This experiment demonstrated that switchgrass, compared to corn, is a reliable and sustainable bioenergy feedstock. This experiment has been a catalyst for other bioenergy projects which have also expanded our understanding of growing and managing bioenergy feedstocks on marginal cropland. We (1) synthesize research from this long-term experiment and (2) provide perspective concerning both the knowledge gained from this experiment and knowledge gaps and how to fill them as well as the role switchgrass will play in the future of bioenergy.